Effects of customer incivility on turnover intention in China's hotel employees: A chain mediating model. (March 2022) - Pu, Bo; Ji, Siyu; Sang, Wenyuan
Abstract: This study explores the relationship between customer incivility and hotel employees' turnover intention in China. The mediating effects of emotional exhaustion, job satisfaction and professional identity were also investigated. The proposed research framework was tested using data from 500 hotel employees who responded to an online questionnaire. The results show that customer incivility affects employees' turnover intention by affecting emotional exhaustion, job satisfaction and professional identity. Among the three mediating variables, the mediating effect of emotional fatigue is the most obvious. When hotel employees encounter customer incivility, it improves their emotional exhaustion, which will reduce job satisfaction, weaken professional identity, and finally lead to the enhancement of turnover intention. Based on conservation of resources theory and cognitive-affective personality system theory, this study proposes a conceptual model of experience development and testing, which enhances the understanding of the relationship between customer incivility and employees' turnover intention and enriches the research on customer incivility.